2010
DOI: 10.1007/s12011-010-8655-8
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Distribution in the Environment as a Limiting Factor for Roe Deer Antler Development

Abstract: The iodine-containing hormones produced by the thyroid gland play a role in the complex neuro-hormonal regulation of antler development. The proper function of the thyroid depends on the adequate iodine supply of the organism, which is directly related to the iodine content of food and drinking water. The purpose of this study was to explore the connection between the iodine content of the water base, which has a strong correlation with the iodine concentration of environmental components available to animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The successful modeling of both body mass and antler score across this gradient was in line with a habitat suitability model proposed for roe deer (Radeloff et al 1999), which assumed large differences in habitat quality among areas of different soil provenance. Similarly, Lehoczki et al (2010) reported a strong effect of 10 levels of soil fertility on roe deer antler size in Hungary. However, the superior performance of the 1-way linear model indicates that the statewide models will be simpler and more accurate using nominal variables in place of soil and forage quality metrics.…”
Section: Discussionmentioning
confidence: 88%
“…The successful modeling of both body mass and antler score across this gradient was in line with a habitat suitability model proposed for roe deer (Radeloff et al 1999), which assumed large differences in habitat quality among areas of different soil provenance. Similarly, Lehoczki et al (2010) reported a strong effect of 10 levels of soil fertility on roe deer antler size in Hungary. However, the superior performance of the 1-way linear model indicates that the statewide models will be simpler and more accurate using nominal variables in place of soil and forage quality metrics.…”
Section: Discussionmentioning
confidence: 88%
“…Experimental work has shown that primates respond to insufficient amounts of dietary iodine with symptoms that are similar to those of modern humans [31]. Even males of red deer living in iodine deficient areas suffer from reduced stag development, which is likely to reduce their fitness [32]. In contrast, wild rodents living under extreme iodine deficient conditions do not differ in their iodine status from populations that have sufficient access to iodine [33].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found no effect of distance of kill site to forest on the occurrence of malformed antlers. Investment in the development of higher quality antlers has been shown to depend on diet not only in roe deer, but also in white‐tailed deer (Harmel et al , Vanpé et al , Lehoczki et al ). Sufficient supplies of nutrients and micronutrients are required for antler development (Brown , Lehoczki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Investment in the development of higher quality antlers has been shown to depend on diet not only in roe deer, but also in white‐tailed deer (Harmel et al , Vanpé et al , Lehoczki et al ). Sufficient supplies of nutrients and micronutrients are required for antler development (Brown , Lehoczki et al ). The single point, kill site, likely did not sufficiently reflect spatial variation in resource quantity and quality of the individual's home range.…”
Section: Discussionmentioning
confidence: 99%